1988
DOI: 10.1515/text.1.1988.8.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Thoughts on text in context: Applying the think-aloud method to text processing

Abstract: The application of the think-aloud method to the study of different text processing tasks is illustrated and discussed. Exploratory studies indicated that some stable general characteristics of think-aloud comment during reading could be found. These characteristics could be categorized reliably in different studies of the reading of various texts. The suggested categories were also sensitive enough to capture the effects of different instructions and texts. In later studies, think-aloud comments were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…However, previous think-aloud studies have shown that significant activities that involve an orientation towards the context (e.g. activation of schemata from long-term memory, the actual reading, the gathering of clues) do not often show up in the protocols as a result of automatization (Waern, 1988). Paraphrasing of the context, however, becomes perceptible in the protocols.…”
Section: A Model Of Deriving Word Meaning From Contextmentioning
confidence: 89%
See 2 more Smart Citations
“…However, previous think-aloud studies have shown that significant activities that involve an orientation towards the context (e.g. activation of schemata from long-term memory, the actual reading, the gathering of clues) do not often show up in the protocols as a result of automatization (Waern, 1988). Paraphrasing of the context, however, becomes perceptible in the protocols.…”
Section: A Model Of Deriving Word Meaning From Contextmentioning
confidence: 89%
“…Three sources may be involved in this, namely internal clues in the word, external clues in the context and personal knowledge from long-term memory, which is automatically activated during reading (Waern, 1988). By gathering information from different sources, a reader selects constraints with which to restrict the word's meaning and to delineate the problem space (Boettcher, 1980;McKeown, 1985).…”
Section: Searching For Cluesmentioning
confidence: 99%
See 1 more Smart Citation
“…Olshavsky (1976Olshavsky ( /1977 placed red dots behind every sentence to prompt readers to think aloud. Waern (1980Waern ( ,1988 instructed her readers to think aloud after reading every sentence. De Jong and Biemans (1988) presented each paragraph of the text on a separate computer screen.…”
Section: Methodsmentioning
confidence: 99%
“…An important starting point for the derivation of coding systems are the works of Gerard Steen, who worked with adult readers (Steen, 1990;1994).He sees the understanding of metaphors as a problem-solving process (see Steen,1990: 301;Steen, 1994: 111), and selects as the basis for his very nuanced categorical system (especially in its early stages) a system developed by Yvonne Waern for identifying problem-solving strategies for understanding of an unknown word (see Waern, 1988).…”
Section: Developing a Coding Systemmentioning
confidence: 99%